(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2023)
3D printing and micromachining of micro-electro-mechanical systems (MEMS) are both technologies with excellent benefits, but also with some limitations. The various 3D printing processes offer a very high degree of design freedom, customizability and efficiency in material usage. Only a few have already achieved micrometer-precise resolutions. They are also very limited in their choice of materials and thus in the type of systems, often being only passive mechanical or fluidic systems. Manufacturing processes from microsystems and semiconductor engineering provide access to a wide range of materials, both conductive and dielectric. There are myriad systems such as sensors, actuators, photonic and electronic devices with resolutions in the micrometer and sub-micrometer range and tremendous integration density. However, although MEMS components are mechanically flexible and moveable in 3D, the typical MEMS designs are based on 2D layouts resulting in planar structures with limited thicknesses. They can be extended to extruded 2.5D structures with high aspect ratios by deep etching, to 3D structures with degrees of design freedom limited to specific crystal orientations by wet chemical anisotropic etching or to even more complex geometries by bonding of structured wafers. The successful combination of 3D printing and micromachining of MEMS is demonstrated in this paper with some basic technology investigations that pave the way to an extended toolbox for MEMS with high degrees of design freedom in 3D as known from 3D printing. Extending the typical one-step manufacturing approach of 3D printing to multiple processing cycles, as is common in manufacturing of microsystems and semiconductor devices, will enable 3D patterning with more complex structures and unprecedented integration density.